2006
DOI: 10.1152/ajpheart.01124.2005
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-1-deficient mice are protected from angiotensin II-induced cardiac hypertrophy

Abstract: -(ADP-ribose) polymerase-1-deficient mice are protected from angiotensin II-induced cardiac hypertrophy. Am J Physiol Heart Circ Physiol 291: H1545-H1553, 2006. First published April 21, 2006 doi:10.1152/ajpheart.01124.2005.-Poly(ADP-ribose) polymerase-1 (PARP), a chromatin-bound enzyme, is activated by cell oxidative stress. Because oxidative stress is also considered a main component of angiotensin II-mediated cell signaling, it was postulated that PARP could be a downstream target of angiotensin II-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 34 publications
7
82
0
Order By: Relevance
“…PARP1, a prototype member of the large PARP family, has been shown to interact with TEF1 to form a complex on M-CAT binding sites of the cardiac troponinT and MHC genes, leading to their muscle-specific gene regulation [136,137]. We as well as others have previously reported that PARP1 is activated during both physiologic and pathologic hypertrophy, and that its levels are further elevated in failing hearts [107,135,138]. A linear correlation was found between the intensity of PARP1 activation and the degree of cardiac hypertrophy, suggesting that the magnitude of PARP activation may have a role in the induction and progression of hypertrophy (Fig.…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 83%
See 2 more Smart Citations
“…PARP1, a prototype member of the large PARP family, has been shown to interact with TEF1 to form a complex on M-CAT binding sites of the cardiac troponinT and MHC genes, leading to their muscle-specific gene regulation [136,137]. We as well as others have previously reported that PARP1 is activated during both physiologic and pathologic hypertrophy, and that its levels are further elevated in failing hearts [107,135,138]. A linear correlation was found between the intensity of PARP1 activation and the degree of cardiac hypertrophy, suggesting that the magnitude of PARP activation may have a role in the induction and progression of hypertrophy (Fig.…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 83%
“…PARP1 induction was also observed in cell-culture models of cardiac hypertrophy induced by treatment of cells with agonists such as angiotensin-II and phenylephrine [135,139]. In regard to what is known about the intracellular stimuli of PARP1, at least two signaling pathways, an increased intracellular Ca 2+ level and the activation of ERK1/2, have been found to activate PARP1 during hypertrophy [140,141].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 92%
See 1 more Smart Citation
“…ionizing radiation and genotoxic compounds) [4]. Conditions that can produce reactive radicals and oxidants within the cell, including hypoxia-reoxygenation [5], elevated extracellular glucose concentration [6][7][8][9], Ca 2+ [10] and angiotensin II [11,12], have been identified as endogenous activators of PARP. Allosteric regulation of auto(poly-ADP-ribosyl) ation by Mg 2+ , Ca 2+ , polyamines, ATP and the histones H 1 and H 3 has also been demonstrated [13].…”
Section: Introductionmentioning
confidence: 99%
“…PARP-1 is involved in pathophysiologies such as hypertension, stroke, neuronal injury, diabetes and inflammation [24] thereby contributing to similar disease states as the RAS. Consistently, animal experiments indicated that cardiac hypertrophy and also endothelial dysfunction induced by angiotensin II are absent in homozygous PARP-1 deficient mice [25,26]. Nevertheless, the regulatory mechanisms of this RAS-PARP interplay are largely unknown.…”
Section: Of 47mentioning
confidence: 97%